Empresas familiares do setor moveleiro e desenvolvimento local em Guarapuava-PR - Grzeszczeszyn, Geverson (2007)
This study analyzes the family businesses in the local development. More specifically, the target of the analysis is the set of furniture industries in Guarapuava - PR city, identified from exploratory study as being family businesses. In this way, two research themes base the study: the household company and local development. The family businesses possess a very important role in the dynamic economy of all the countries, and most of the companies in the world are family businesses. The interaction among family and company gives to these organizations a peculiar complicity, observing that, in both of them there are reason (economic market rationality), and emotion (feelings from household relationships). These confluences create family businesses characteristics challenges, as the household conflicts management, the professionalization and the succession. The local development, in its turn, reflects the dissatisfaction of the society with centered national and regional projects of development that do not create significant transformations in local level. The local development is based on the protagonism of the society, that is, in the community participation (people and organizations), as its destination constructor. Thus, from diagnosis and, especially the identification of local potentialities, the social actors - people, organizations/institutions and public power - in the construction of a better future for the society articulate themselves. In this process, factors as capital stock, human capital, social nets, popular organization, public politics, education, cooperation, negotiation and solidarity are key-element for the local transforming dynamics promotion. For the achievement of this study, the data triangulation technique was used, displaying and analyzing simultaneously multiple realities. In the first stage of the research, of quantitative nature, the profile of furniture family businesses was identified; in the second stage, of qualitative nature, the interpretation of the public power was searched, the current management and last managements; of entrepreneurs and former-entrepreneurs of the furniture industry; beyond the collection of secondary data; to apprehend the participation of family businesses of the furniture industry of Guarapuava city in the local development. The results show that most of the household cabinet-makers companies of Guarapuava possess common characteristics to the micron and small family businesses: the company is the main source of the family income; the organizational processes are, in many cases, informal and the property of the organization is in the founding proprietor hands. Most of them work with the furniture production by size (cabinet-makers), having only two industries, of a small average, acting total with the in series furniture production. The family businesses participation of the furniture industry in the local development in Guarapuava occurs by means of: constitution of informal social nets of cooperation between cabinet-makers entrepreneurs; participation in business-oriented partnerships between the cabinet-makers entrepreneurs and other enterprise categories; joints of cabinet-makers entrepreneurs with the public power in the creation and execution of public initiatives for the sector; and other contributions as: generation of jobs; payment of tributes; diverse donations; general aids to the people and entities; and philanthropic participation in institutions.